How to Determine the Meaning of a Sacred Text Cases and Methodologies. - Williams, Jay G. (Lewiston : The Edwin Mellen Press, 2011)
This work applies many different approaches to the analysis of sacred texts. The articles contained in this collection are influenced by structuralism, phenomenology, the study of self-referentiality and Zen. In many cases, Eastern thought is applied to Western texts, and vice versa.
Title Page; Copyright Page; WIlliams PDF ISBN 0-7734-2035-5; Preface; Foreward; Dedication; Acknowledgements and Permissions; TABLE OF CONTENTS; Introduction; Part I; Part II; Part III; Part IV; Part V; Part VI; Epilogue; Works Cited; Indices
Description based upon print version of record.
Keywords: Hermeneutics; Sacred books -- History and criticism; Sacred books; Religion; Sacred books -- History and criticism; Hermeneutics; RELIGION / Christianity / General; Electronic books